Clinical significance of quantitative assessment of glucose utilization in patients with ischemic cardiomyopathy - Ko, Kuan-Yin; Wang, Shan-Ying; Yen, Ruoh-Fang; Shiau, Yu-Chien; Hsu, Jung-Cheng; Tsai, Hao-Yuan; Lee, Chien-Lin; Chiu, Kuan-Ming; Wu, Yen-Wen (Journal of nuclear cardiology, 2020)
The aim of this study was to prospectively quantify the rate of myocardial glucose uptake (MRGlu) in myocardium with different perfusion-metabolism patterns and determine its prognostic value in patients with ischemic cardiomyopathy. 79 patients with ischemic cardiomyopathy were prospectively enrolled for dynamic cardiac FDG PET, and then followed for at least 6 months. Perfusion-metabolism patterns were determined based on visual score analysis of 201Tl SPECT and FDG PET. MRGlu was analyzed using the Patlak kinetic model. The primary end-point was cardiovascular mortality. Significantly higher MRGlu was observed in viable compared with non-viable areas. Negative correlations were found between MRGlu in transmural match and a history of hyperlipidemia, statin usage, and triglyceride levels. Diabetic patients receiving dipeptidyl peptidase-4 inhibitors (DPP4i) had a significantly lower MRGlu in transmural match, mismatch, and reverse mismatch. Patients with MRGlu in transmural match ≥ 23.40 or reverse mismatch ≥ 36.90 had a worse outcome. Myocardial glucose utilization was influenced by substrates and medications, including statins and DPP4i. MRGlu could discriminate between viable and non-viable myocardium, and MRGlu in transmural match and reverse mismatch may be prognostic predictors of cardiovascular death in patients with ischemic cardiomyopathy.